Theorizing embodied, collective and societal learning through prefigurative social movements - Margaret L. Cain; Jennifer Kushner; Cassidy Thomas (Adult Education Research Conference, 2021)
This paper theorizes adult learning as a multi-leveled, emergent process of interactions between individuals, groups, and societal systems. We theorize from the context of prefigurative social movements that are enacting values of direct democracy, solidarity economics, and equity. We analyze Occupy encampments as sites in which individuals, movement groups, and society learn as complex adaptive systems. The theorizing of these learning processes has implications for adult education theory, research, and practice.
Keywords: social movement learning; systems thinking; adult learning theory; prefigurative movements